Characterization of Fe-doped ZnO from kaffir lime extracts for antibacterial applications - Lauthfi, Muhammad Asyraf Al-Wafiy; Mohd Yusoff, Mohd Zaki; Kamil, Suraya Ahmad; Syed Mohamad, Sharifah Aminah; Nur Ubaidah Saidin, Nur Ubaidah (UiTM Press, 2025)
In this work, ZnO nanoparticles were doped with ferrum metal to improve their ability to interact more with the bacteria. The process to fabricate ZnO is called the biosynthesis method, using lime extract to grow the ZnO nanoparticles. After the chemical process was completed, the surface morphology, and structural properties of the sample was evaluated by FESEM, EDS, and XRD measurements. XRD measurement shows a good crystalline quality of Fe-doped ZnO nanoparticles. EDS measurement is confirmed the existence of Zn, O, Fe elements in the sample. We investigated the antibacterial activity of Fe-doped ZnO NP samples at 1 mg/ml against E. coli and S. aureus. The result from the antibacterial activity of Fe-doped ZnO NP samples at 1 mg/ml against S. aureus shows that there was a 10 ± 0.6 mm inhibition zone for the mixed Fe-doped ZnO and 10% DMSO, indicating moderate activity.